The Importance of Effective Access to Justice for Charter Violations and the Role of the Court Challenges Program - Samson, Marika Giles (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2023)
This paper argues that the Canadian Charter of Rights and Freedoms can only deliver on its promises when those who benefit from its guarantees are able to challenge government action in courts. This is true both in considering the Charter as a constitutional document and as a human rights instrument. As such, we must be concerned about whether rightsholders have effective access to the courts to bring such cases, particularly given the long-term crisis in access to justice in Canada. Finding that access is often out of reach, the paper then considers the role that the Court Challenges Program, a publicly funded not-for-profit organization that provides funding to groups and individuals seeking to bring Charter challenges, can and does play in creating pathways for accessing Charter justice.